Women Leaders: The Next Chapter - Palma-Angeles, Antonette (Archīum Ateneo, 2021)
This chapter on women leaders discusses how even as women are reputedly empowered in the Philippines; the number of women leaders has been fluctating in the last 5 years and women occupy only select positions (traditionally reserved for women) both in the public (Secretaries of the Departments of Tourism and Social Welfare and Development) and private sectors (finance and HR). Few women are in boards and are CEOs. The two female preisdents rose to the Presidency because of their association with prominant male politicians. The paper proposes interventions on how women can be further empowered so that they can rise to leadership positions which they richly deserve and are most qualified.